2021
DOI: 10.1093/treephys/tpab100
|View full text |Cite
|
Sign up to set email alerts
|

Parenchyma underlies the interspecific variation of xylem hydraulics and carbon storage across 15 woody species on a subtropical island in Japan

Abstract: Parenchyma is an important component of the secondary xylem. It has multiple functions and its fraction is known to vary substantially across angiosperm species. However, the physiological significance of this variation is not yet fully understood. Here, we examined how different types of parenchyma (ray and axial parenchyma, and axial parenchyma in direct contact with vessels [APV]) are coordinated with three essential xylem functions: water conduction, storage of non-structural carbohydrate (NSC), and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 89 publications
3
24
1
Order By: Relevance
“…We did not find significant relationships between NSCs and %RAP in subtropical and tropical tree species, therefore partially refuting our first hypothesis. Because our results are contradictory to the results of Kawai et al (2021), who found that RAP fractions were significantly associated with NSC content in the branches of 15 subtropical woody species, our low sample size (21 species) might not fully represent the variability in NSCs and RAP encountered in these climates. Additionally, RAP performs several major functions in tropical species, such as water storage and defense against pathogens, that may be less important in temperate species (Plavcová et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not find significant relationships between NSCs and %RAP in subtropical and tropical tree species, therefore partially refuting our first hypothesis. Because our results are contradictory to the results of Kawai et al (2021), who found that RAP fractions were significantly associated with NSC content in the branches of 15 subtropical woody species, our low sample size (21 species) might not fully represent the variability in NSCs and RAP encountered in these climates. Additionally, RAP performs several major functions in tropical species, such as water storage and defense against pathogens, that may be less important in temperate species (Plavcová et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Parenchyma fractions might act as a proxy for NSC storage capacity, and recent studies showed positive correlations between RAP and NSC content in woody stems and branches (Plavcová et al, 2016; Godfrey et al, 2020; Chen et al, 2020; Kawai et al, 2021; Pratt et al, 2021). Although, these studies focused on a limited number of species, data suggest that the roles of RP and AP are distinct among species and climates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as transpiration creates negative hydraulic pressures, surrounding tissues should, if hydrated, be able to provide water to the vascular tissues to reduce the risk of embolism. The structural mechanisms responsible for enhancing the water storage capacity in trees are underpinned by the anatomical configuration of the woody tissues with both capillary storage compartments (i.e., open vessels, tracheids, fibers, intercellular spaces, and cracks) and elastic storage compartments (i.e., living parenchyma cells) likely to be relevant ( Borchert and Pockman, 2005 ; Scholz et al, 2008 ; Jupa et al, 2016 ; Kawai et al, 2021 ). Not only the anatomic features define plant water storing capacity but also the chemical compounds with osmotic activity play an essential role in plant osmotic adjustment ( Turner and Jones, 1980 ; Turner, 2018 ; Signori-Müller et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that trade‐offs between secondary xylem and leaf structure promote adjustments concerning rates of water supply, hydraulic conductivity (Cosme et al, 2017; Olson, 2020), and embolism resistance (Lens et al, 2011; Li et al, 2016; Skelton et al, 2018). Such changes involve the distribution and volume of different cell types of secondary xylem (Tng et al, 2018; Percolla et al, 2021; Kawai et al, 2022); the frequency, grouping, and width of vessel elements (Dória et al, 2016); the thickness of the intervascular pit membrane (Plavcová et al, 2011; Dória et al, 2018); the degree of wood density (Chave et al, 2009; Ziemińska et al, 2020); and the amount of leaf area and stomatal density (Rossatto and Kolb, 2013). These adjustments can occur in varied combinations, and knowing the relative contribution of each to support continued water transport at the species level can help reveal plant strategies to survive different environments.…”
mentioning
confidence: 99%